2019
DOI: 10.1186/s13195-019-0514-z
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional and longitudinal characterization of SCD patients recruited from the community versus from a memory clinic: subjective cognitive decline, psychoaffective factors, cognitive performances, and atrophy progression over time

Abstract: Background Subjective cognitive decline (SCD) defines a heterogeneous population, part of which having Alzheimer’s disease (AD). We aimed at characterizing SCD populations according to whether or not they referred to a memory clinic, by assessing the factors associated with increased AD risk. Methods Seventy-eight cognitively unimpaired older adults from the IMAP+ study (Caen) were included, amongst which 28 healthy controls (HC) and 50 SCD recruited from the community … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 97 publications
6
27
0
Order By: Relevance
“…Finally, the reported link between an individual's own cognitive concerns (rather than those of an informant) and AD biomarkers in asymptomatic individuals suggests that there may be additive utility in examining trajectories of cognitive complaints alongside cognitive decline to predict risk for clinical progression . This may also be extended to measures of mild neurobehavioral changes as well as potentially novel measures of health outcomes developed in coordination with patient and caregivers to better identify what is of value from an individual's perspective (e.g., driving, perceived competence, etc).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the reported link between an individual's own cognitive concerns (rather than those of an informant) and AD biomarkers in asymptomatic individuals suggests that there may be additive utility in examining trajectories of cognitive complaints alongside cognitive decline to predict risk for clinical progression . This may also be extended to measures of mild neurobehavioral changes as well as potentially novel measures of health outcomes developed in coordination with patient and caregivers to better identify what is of value from an individual's perspective (e.g., driving, perceived competence, etc).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the reported link between an individual's own cognitive concerns (rather than those of an informant) and AD biomarkers in asymptomatic individuals 26 suggests that there may be additive utility in examining trajectories of cognitive complaints alongside cognitive decline to predict risk for clinical progression. 27 This may also be extended to measures of mild neurobehavioral changes [28][29][30]…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps individuals who are concerned about their cognitive ability and seek medical advice represent older adults with SCD more likely to harbor incipient neurodegeneration while individuals recruited from the general public may include SCD cases in an early disease phase, or cases due to neuroticism, poor sleep, or transient stressful life events. The extant literature suggests that recruitment methods may indeed contribute to SCD sample characteristics, with cohorts recruited from memory clinics exhibiting poorer neuropsychological performance, greater hippocampal atrophy, greater cortical atrophy over time, and greater depression than cohorts recruited from the general population that have not sought medical help [93][94][95]. However, as samples that have sought medical help have exhibited both increased and decreased functional connectivity cross-sectionally [18,30,47], the impact of the severity of cognitive complaint on functional metrics is not as clear.…”
Section: Brain Network Functional Connectivity In Subjective Cognitivmentioning
confidence: 99%
“…In addition, studies have suggested that the recruitment sources for SCD studies may have a significant influence on study outcomes. For instance Kuhn et al (2019) found higher atrophy progression over time and a relatively smaller proportion of APOE ε4 carriers in patients from an SCD clinic compared SCD patients from the community. This finding reinforced their previous study, which found that those who seek consultation are at a higher risk of developing Alzheimer's clinical syndrome (Perrotin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It indicated that SCD-clinic patients may constitute a more vulnerable population than SCD-community patients. They may be at increased risk for cognitive decline and possibly Alzheimer's clinical syndrome (Kuhn et al, 2019).…”
Section: Introductionmentioning
confidence: 99%